Manajemen Risiko Penyakit Akibat Kerja di Industri Roti - Hanani, Atidira Dwi (Preventif : Jurnal Kesehatan Masyarakat, 2023)
The rendang bread industry is one of the bakery industry in Palembang that has various risks of occupational diseases. This study aims to identify, analyze, and evaluate health risks in the work environment of the rendang bread industry which can cause occupational diseases and develop control recommendations so that occupational diseases do not arise which can be detrimental to workers and the industry. This research is a semi-quantitative research. Data was collected by observation and interviews. The data processing method in this study uses the HIRA (Hazard Identification and Risk Assessment) method. The results showed that there were 21 kinds of risks in the production process of rendang bread with 9.52% extreme risk, 38.10% high risk, 47.62% moderate risk and 4.76% low risk. Risk control that can be carried out for the rendang bread production process is by eliminating unsafe equipment, replacing unsafe tools and materials with safer ones, redesigning the work environment, providing education to workers, encouraging changes in worker behavior to improve safety and health in work, as well as the use of personal protective equipment appropriate to the type of work.